Features of psychological correction work with family system within client-centered therapy - A. Ivashchenko, (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The problems of existing theoretical and practical approaches in family pschotherapy are considered in the article. The general recommendations for the correctional work with family system (marriage subsystem) are proposed in frames of client-centered therapy.
Keywords: family system; family; a young family; a married couple; client-centered therapy; psychological correction of marital relations